The Family Medicine Physicians - Nurse Collaboration and Its Relation to Patients' Safety Climate - Sultan Sami Shaqra,; Malak Abdulaziz Khiro,; Ruba Yasir Bahadur,; Emad Meshal Burayk Alotaibi,; Saeed Ahmed Ali Alomari,; Saeed Abdullah Mohammed Al-Zahrani,; Amnah Abdu Mohammed Abutaleb,; Abdullah Mesfer Ali Alghamdi,; Layla Hamad Halloush Moqree,; Sadia Marzoug Almoalad, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Quality of treatment and patient safety are linked to nurses and doctors working together effectively. The objective is to evaluate the relationship between patient safety climate in critical care units and nurse-physician teamwork. Research design : Correlational research design was employed. Setting: King Abdullah Medical City-Mkkah's Family Medicine department served as the study's site. 90 physicians and 210 nurses made up the convenience sample. Two tools were utilized. Tool I, the Collaborative Practice Scale, is a two-part instrument used to evaluate the collaborative behavior of doctors and nurses. Part 1 asks about personal qualities. Tool II: Patient safety climate survey to gauge how doctors and nurses feel about patient safety climate. The results : showed that both nurses and doctors exhibited a neutral degree of collaborative behavior; overall, nurses' collaborative behavior was higher (58.35) than doctors' (55.25). Physicians and nurses also had a neutral opinion of the patient safety environment. Compared to doctors (126.564), nurses exhibited a higher percentage of regard for the patient safety climate (144.585). Conclusion: there was significant correlation between nurses-physician collaborative behavior and patient safety climate. Recommendations: conduct in service program and workshop about team work and patient safety and development of an inter-professional collaborative environment to increase nurses’ performance as well as improve patient safety climate.